Responses of four shrub species to four levels of irrigation in a semi-arid environment - Smith, Jason F., author; Klett, James E., advisor; Andales, Allan A., committee member; Bauerle, William L., committee member (Colorado State University. Libraries, 2012)
In response to a severe regional drought that afflicted much of Colorado in 2002, Colorado State University initiated a study to determine the impacts of progressively decreasing irrigation treatments on some common shrub species. Irrigation treatments were based on the evapotranspiration of a short reference crop (ETo). In 2008, four shrub species were planted for trialing: Cornus sericea L. 'Isanti' (redosier dogwood), Hydrangea arborescens L. 'Annabelle' (smooth hydrangea), Physocarpus opulifolius (L.) Maxim. 'Monlo' (Diablo® ninebark) and, Salix pupurea L. 'Nana' (arctic blue willow). In addition to the shrubs, Poa pratensis L. (Kentucky bluegrass) was used as a control. After giving the shrubs and turf one growing season to establish, treatments were applied in 2009 and 2010. The study was comprised of a field component and a lysimeter component. The field component had four treatments based on ETo (0%, 25%, 50%, and 100%) and the lysimeter component had three treatments (25%, 50%, and 100%). All four species were planted in the field component and only the redosier dogwood and smooth hydrangea were planted in the lysimeter component due to space limitations. Data collection in both components included canopy height and width, visual ratings, predawn leaf water potentials, end of season leaf area, and end of season leaf fresh/dry weights. The field component also included soil moisture readings, osmolality, and infrared readings of the Kentucky bluegrass. The lysimeter component required daily weight measurements during dry down periods. As watering amounts increased for the field dogwoods, ninebarks, and willows various characteristics (overall stress, aesthetic appeal, size, osmolality) were also positively affected. However, all tested replicates of these three species in the 0% treatment appeared acceptable for landscape use, as well. The hydrangeas in the 100% treatment had the highest visual ratings. In addition, the water potentials were more negative in the 100% treatment. Due to the visual ratings and water potential data, it suggests that smooth hydrangea needs more than 100% ETo to improve growth and performance. All of the field hydrangeas in the 0% treatment were unacceptable for landscape use and were close to death, however, 80% of the replications survived until the conclusion of the experiment. As such, the smooth hydrangea can survive a short period without water and should recover when water becomes available. The lysimeter dogwoods and hydrangeas adjusted their growth habits based on water availability. Water was used on a daily basis at a faster rate as the irrigation treatments increased. The lysimeter shrubs in the 100% treatment used more water on a daily basis than the 50% treatment and the 50% treatment used more than the 25% treatment. The increased water use affected plant growth and if more water was available to the dogwood and hydrangea, a larger plant resulted.
Keywords: dogwood; evapotranspiration; hydrangea; ninebark; plant water use; willow